Intersecções entre a estética da recepção e o romance policial brasileiro contemporâneo: a elegia do menor pela recepção estética - Leidens, Alexandre (2019)
This work aims at approaching the Aesthetics of Reception with contemporary Brazilian Detective fiction, in order to constitute an interstitial analysis, observing argumentative fields of theory as support to the narrative probabilities of the literary genre. The basic prerogatives of the studies of Jauss (1967, 1979), Stierle (1979) and Lima (1979, 2006) will be used as a principle for the study of the School of Constance. From Jauss will be observed some essential characteristics of the theory, such as the considerations about the historical horizon and the expectations horizon of the reader and society in a macro construct; the studies of Stierle will be support for reflections focused on the relation of the reader with the reception of abstract texts and in the reflections on formal questions of the narrative; Lima will be the basis for critical thinking about the theory of reception itself. In addition, later reflections on reception aesthetics will be used for a broader observation on the subject both in its prerogatives and in its development, reaching studies that were constituted and highlighted using conjectures of the School of Constance and, from this, suggested new reflections and theorized about not only reception but also other possibilities. This part of the study will be supported by authors such as Eco (1994); Eagleton (2006); Rocha (2003) and Frye (2017). In these theorists, we will look for some considerations that may be useful at different moments in the argument regarding reception. The theory of reception and the thoughts to it later will be crucial to subsidizing an argument about the detective fiction. The genre will be observed in light of the theory and some of its characteristics will be evaluated based on it. However, in order to analyze the detective fiction, its main foundations will be evidenced, in view of its classic constitution and the contemporary detective fiction, also highlighting the modifications that have been made to it over time. As a subsidy for the reflection about the detective fiction, will be used studies of Mandel (1988); Reimão (2005); Massi (2011), among others. Mandel and Reimão will be support for reflections on the insertion of the detective fiction in an academic environment, evaluating its basic constructs and its possibilities as a literary genre; Massi will subsidize the whole comparative perspective between the detective fiction in the classic molds and in contemporary lines. The researches of the three scholars will be fundamental both for a theoretical support in gender and for the observation of the detective fiction under the reception aesthetics, which will also focus on the analysis of fragments of contemporary Brazilian detective works by authors such as Garcia- Roza (1996, 1999, 2001, 2004, 2005, 2006, 2007, 2009, 2012); Montes (2010; 2014; 2015; 2016); among others. The work will be qualitative, it’s approach will be bibliographical, stressing the relations between theory and gender, seeking to build a solid theoretical framework for theorizing the perspective of valorization to detective fiction based on the presuppositions of reception.